2016
DOI: 10.1155/2016/3103672
|View full text |Cite
|
Sign up to set email alerts
|

IncF Plasmids Are Commonly Carried by Antibiotic ResistantEscherichia coliIsolated from Drinking Water Sources in Northern Tanzania

Abstract: The aim of this study was to identify the replicon types of plasmids, conjugation efficiencies, and the complement of antibiotic resistance genes for a panel of multidrug resistant E. coli isolates from surface waters in northern Tanzania. Standard membrane filtration was used to isolate and uidA PCR was used to confirm the identity of strains as E. coli. Antibiotic susceptibility was determined by breakpoint assay and plasmid conjugation was determined by filter-mating experiments. PCR and sequencing were use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(27 citation statements)
references
References 40 publications
2
25
0
Order By: Relevance
“…The dissemination of ESBL genes is reportedly mediated by the IncI1 plasmid [21]. E. coli was also reported to maintain the IncI1 plasmid without antibiotic selection pressure [22]. Thus, our findings suggested that the IncI1 plasmid has an important role in the spread of bla CTX-M-2 in racehorses.…”
Section: Discussionsupporting
confidence: 53%
“…The dissemination of ESBL genes is reportedly mediated by the IncI1 plasmid [21]. E. coli was also reported to maintain the IncI1 plasmid without antibiotic selection pressure [22]. Thus, our findings suggested that the IncI1 plasmid has an important role in the spread of bla CTX-M-2 in racehorses.…”
Section: Discussionsupporting
confidence: 53%
“…The mating was done as described previously [ 25 ]. Donor strains were grown on LB (Luria-Bertani) plates containing antibiotics (as per donor’s antibiotic resistance listed in Table 2), from frozen stocks, by overnight incubation at 37 °C.…”
Section: Methodsmentioning
confidence: 99%
“…The procedure was carried as described by Robinson and Batt (1999) and Lyimo et al (2016). Briefly, 10ml of milk sample was diluted into 90ml of double distilled sterile water.…”
Section: Isolation Of E Colimentioning
confidence: 99%